A Theory of Partially Directed Search - Menzio, Guido (Journal of Political Economy, 2007)
This article studies a search model of the labor market in which firms have private information about the quality of their vacancies, they can costlessly communicate with unemployed workers before the beginning of the application process, but the content of the communication does not constitute a contractual obligation. At the end of the application process, wages are determined as the outcome of an alternating offer bargaining game. The model is used to show that vague noncontractual announcements about compensation—such as those one is likely to find in help wanted ads—can be correlated with actual wages and can partially direct the search strategy of workers.